Numerical analysis of Al2O3/water nano-fluid natural convection in a square cavity filled with an anisotropic porous medium under a magnetic field - Safi, S.; Berrahil, F.; Filali, A.; Benissaad, S. (Archives of Mechanics, 2025)
Natural convection in porous media is crucial for applications such as geothermal energy cooling systems and energy storage, where efficient heat transfer is essential. However, the combined effect of anisotropy in the porous matrix and an inclined magnetic field on nanofluid heat transfer remains poorly understood hence, this study addresses numerically the unexplored combined effects of anisotropy and inclined magnetic field on the natural convection of water-based Al2O3 nanofluid. The Darcy–Brinkman–Forchheimer model and energy transport equations describe nanofluid motion and heat transfer in a porous medium. The mathematical equations are discretized using the finite volume method in an in-house computer code. The governing parameters are the Rayleigh number the Darcy number, the Hartmann number, solid volume fraction, the permeability ratio K (a measure of porous medium anisotropy) and an inclination angle with the magnetic field. Results are reported for streamlines, temperature contours, and the average Nusselt number under different parametric conditions. It was found that increasing the Rayleigh and Darcy numbers shifts the system from conduction to convection, improving the heat transfer rate. The nanoparticle volume fraction enhances heat transfer in conduction-dominated flows but reduces it in convection-dominated regimes. A higher Hartmann number decreases the average Nusselt number, with a more pronounced effect when the magnetic field is oriented horizontally. A higher permeability ratio reduces flow resistance and enhances convective heat transfer, but beyond K > 10, further increases in permeability have minimal impact on the heat transfer rate.